Persepsi Penerimaan Diri dan Keterikatan Sosial: Pergeseran Penggunaan Bahasa Daerah pada Generasi Z di Wilayah Aceh Tengah - Yana Nazela Ilma; Wahna Nurianda; Tariza Yuvi Yolanda Spreckhelsen; Qurratu Meutia Balqis; M. Miftahul Rizki Tantri; Risydah Fadilah; Suaidah Lubis (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the meaning of self-acceptance and social belonging in the phenomenon of regional language shift among Generation Z in the Gayo region, Aceh Tengah. The declining use of the Gayo language among youth has been accelerated by globalization, modernization, digital media exposure, and the stigma that local languages are considered “outdated” in contemporary social interactions. Unlike previous sociolinguistic studies that emphasized structural and functional factors, this research adopts a psychological perspective by focusing on internal dynamics such as self-acceptance and social belonging. Using a qualitative phenomenological approach, this study was conducted in Takengon, Aceh Tengah, involving three Generation Z participants aged 20–23 of Gayo ethnicity. Data were collected through in-depth interviews, behavioral observations, and documentation. Data analysis followed phenomenological procedures including horizonalization, theme clustering, and individual textural description. The findings reveal that although a functional shift toward Indonesian and foreign languages has occurred, participants generally demonstrate positive affective self-acceptance toward their ethnic identity. However, limited Gayo vocabulary and lack of fluency reduce their confidence when interacting with older native speakers, sometimes leading to feelings of inferiority or perceived out-group status in their own cultural setting. Social belonging among participants appears value-centric rather than linguistically centric, rooted in strong family ties and collective memory. Interestingly, digital Gayo-language content functions ambiguously: it strengthens symbolic belonging while simultaneously highlighting participants’ linguistic limitations. The study recommends the creation of safe linguistic spaces to support intergenerational language practice without judgment, fostering both self-acceptance and sustainable cultural continuity.